2014
DOI: 10.1167/iovs.14-15531
|View full text |Cite|
|
Sign up to set email alerts
|

Serum Homocysteine, Vitamin B12, and Folate, and the Prevalence and Incidence of Posterior Subcapsular Cataract

Abstract: Higher serum homocysteine level was associated with PSC prevalence in this population. Vitamin B12 status seemed to modify this association. Lack of longitudinal association could have resulted from insufficient study power.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
1
12
1
Order By: Relevance
“…3941 Previous observational data for these nutrients, derived from several small cross-sectional and case-control studies, generally indicate an inverse association between dietary or blood levels and risk of cataract. 1624 Thus, our finding of no significant effect overall, but significant increases in the PSC subtype, and extraction of all 3 subtypes, in the combined treatment group contrasts with previous observational data. Given the high dose of folic acid, vitamin B 6 , and vitamin B 12 used in the WAFACS, one interpretation of these findings is that the optimal dose for cataract prevention may be lower than the high doses tested in this trial.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…3941 Previous observational data for these nutrients, derived from several small cross-sectional and case-control studies, generally indicate an inverse association between dietary or blood levels and risk of cataract. 1624 Thus, our finding of no significant effect overall, but significant increases in the PSC subtype, and extraction of all 3 subtypes, in the combined treatment group contrasts with previous observational data. Given the high dose of folic acid, vitamin B 6 , and vitamin B 12 used in the WAFACS, one interpretation of these findings is that the optimal dose for cataract prevention may be lower than the high doses tested in this trial.…”
Section: Discussioncontrasting
confidence: 99%
“…Folic acid and vitamins B 6 and B 12 have also been linked with lower rates of cataract in observational studies, 1624 but have not yet been tested in randomized trials of cataract prevention. In addition to their antioxidant capabilities, 2528 these nutrients exhibit other physiological actions including a well-established homocysteine-lowering effect, 29 and enhanced bioavailability of nitric oxide (NO), 30,31 that might also affect cataract development…”
Section: Introductionmentioning
confidence: 99%
“…We calculated the required sample size for plasma tHcy and MTHFR measurement based on results from the Tan et al's [ 11 ] study which reported a mean difference of tHcy levels of 1.9μmol/L, a standard deviation of 4.8μmol/L in their population. Under the Type I error rate of 0.05 and a statistical power of 90%, 141 ARC patients and 141 healthy controls were randomly selected from the whole samples.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular studies have demonstrated that raised Hcy induced apoptosis by increasing ROS generation through activation of p38 MAPK [ 8 ], and down-regulating antioxidant enzymes such as heme oxygenase-1 and glutathione peroxidase [ 9 , 10 ]. Additionally, elevated plasma total Hcy (tHcy) levels were found to be associated with increased risk of ARC in two clinical studies [ 11 , 12 ]. Methylenetetrahydrofolate reductase (MTHFR) is the key enzyme for Hcy metabolism that catalyzes the conversion of 5, 10-methyltetrahydrofolate to 5-methyltetrahydrofolate, a methyl donor during the remethylation of Hcy [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two other studies of dietary and serum levels of folate showed conflicting results. 49,50 A randomized placebo-controlled trial of Centrum found that those taking the multivitamin had a two-fold increased risk in PSC events. 51 No increased mortality risk was associated with any B vitamin or lutein/zeaxanthin intake levels.…”
Section: Discussionmentioning
confidence: 99%